Ecological complexity and the management of common property resources - Turner, Matthew A. (Land Tenure Center, Nelson Institute of Environmental Studies, University of Wisconsin, 2007)
Many community-based conservation programs are designed without carefully considering goals, community capacities, and the ecology of the common property resource. This LTC Brief outlines factors that can improve common property management.
8 p.
Keywords: Community-based conservation; Commons; Natural resources, Communal Developing countries Management